Educational techniques between reality and ambition: (comparative study) - AL-Janabi, Omar Falah; AL-Sadi, Ameer Mohammed (Al-Adab Journal, 2020)
The aim of the research is to identify the modern educational techniques available in the public and private schools affiliated to the Directorate of Education of Karbala.In order to verify the research objective, the following questions were formulated: What are the modern educational techniques available in the public and private schools affiliated to the Department of Education of the Holy Karbala / Center?Are there statistically significant differences at the level of significance (0.05) between the responses of the sample according to gender variable?Are there statistically significant differences at the level of significance (0.05) among respondents of the sample according to the variable of the school stage?Are there statistically significant differences at the level of significance (0.05) between the responses of the sample according to the variable type of study?To answer these questions, a questionnaire consisting of (12) items was directed at a sample of the public and private school administrations in the center of Karbala governorate, which was chosen according to the class method, reaching (141) school administration with (75) managers and (66).The research reached: The educational techniques available in a large number of public schools are (cassette recorder, camera, microscope), but in private schools (camera, cassette recorder, internet, smart screen)The educational techniques available in a few schools in the government are (Internet, laptop) in the private schools is a (microscope).There were no statistically significant differences at the level of significance (0.05) between the responses of the sample according to the gender variable.There were no statistically significant differences at the level of significance (0.05) between the responses of the sample according to the variable stage.There were statistically significant differences at the level of significance (0.05) among the responses of the sample according to the type of study variable and in favor of the private schools.